Comparative evaluation of echocardiography indices during the transition to extrauterine life between small and appropriate for gestational age infants - Suciu, Laura Mihaela; Giesinger, Regan E.; Mărginean, Claudiu; Muntean, Mihai; Cucerea, Manuela; Făgărășan, Amalia; McNamara, Patrick (Frontiers in Pediatrics, 2023)
Objectives: To study changes in heart function and hemodynamics during the transitional period in small for gestational (SGA) infants and appropriate (AGA) healthier counterparts. Design: A hospital based prospective observational study was performed at a perinatal center. Echocardiograms were performed on the first postnatal day and again at 48 hours age. Term SGA infants were compared with those AGA newborns matched for the GA and mode of delivery. Results: Eighteen SGA infants were compared with 18 AGA infants [gestation 38±1.5 vs 38±1.2 weeks, p>0.05 and birthweight 2331±345 vs 3332 ±405 grams, p<0.05, respectively]. Maternal weight and body mass index was higher among non-affected pregnancies, 61% infants were born vaginally, and no differences in cord blood pH at birth were noted. SGA infants had higher systolic and mean blood pressure at both time points, lower indices of right ventricular (RV) performance [TAPSE (tricuspid annular peak systolic excursion) 7.4 ± 2.8 vs 9.3±0.7 on day 1, 7.2±2.8 vs 9.2±0.5 on day 2, p=0.001], lower pulmonary acceleration time (PAAT) suggestive of elevated pulmonary vascular resistance [56.4±10.5 vs 65.7±13.2 on day 1, 61.4±12.5 vs 71.5±15.7 on day 2, p=0.01] and higher left ventricular (LV) ejection fraction [62.1±7.8 vs 54.9±5.5 on day 1, 61.9±7.6 vs 55.8±4.9 on day 2, p=0.003]. Conclusions: SGA infants had evidence of higher pulmonary vascular resistance, and lower RV performance during the postnatal transition. The relevance and impact of these changes to hemodynamic disease states during the postnatal transition requires prospective investigation.